Hypothetical P63/mmc-Type CsCrCl3 Ferromagnet: Half-Metallic Property and Nodal Surface State - Li, Yang (Frontiers in Materials, 2020)
This work is focusing on the electronic, magnetic, half-metallic behaviors, and interesting surface state of hypothetical CsCrCl3 ferromagnet with P63/mmc space group that are investigated under the spin-polarized Generalized Gradient Approach (GGA) and spin-polarized GGA plus Hubbard U correction within the framework of the Density Functional Theory (DFT). The calculated total magnetic moment of P63/mmc CsCrCl3 is ~7.397 µB, and the mainly contribution to the total magnetism is coming from the Cr atoms. Based on obtained spin-polarized band structures, we confirmed that this hypothetical CsCrCl3 is a half-metal with 100% spin-polarization. Without spin-orbit coupling, i.e., the spin and the orbit degrees of freedom are dependents, we found that there should be a interesting nodal surface state at kz = plane due to P63/mmc type lattice structure enjoys a two-fold screw axis S2z. Our study can be seen as a strong evidence to exhibit that the protected nodal surface state can be achieved in magnetic materials.